Pengaruh Teamwork, Loyalitas Pegawai terhadap Komitmen Organisasi dengan Motivasi sebagai Variabel Intervening : (Studi pada MTs Unggulan Darul Hikam) - Nabila Zulfa Mawaddah; Imam Baidlowi; Kasnowo Kasnowo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study is motivated by the importance of organizational commitment in supporting the success of educational institutions, particularly at MTs Unggulan Darul Hikam Mojokerto. Organizational commitment is essential for achieving the long-term goals of an institution, and it is influenced by various factors, including teamwork and employee loyalty. Work motivation plays a critical role as a mediating variable that connects these factors. The purpose of this research is to analyze the influence of teamwork and employee loyalty on organizational commitment, with motivation as an intervening variable. To achieve this, a quantitative approach was employed with a census method, involving 52 employees as respondents. Data were collected using questionnaires, which were tested for validity and reliability. The analysis utilized multiple linear regression, path analysis, and the Sobel test to determine the relationships between the variables. The results revealed that both teamwork and employee loyalty significantly impact organizational commitment, both directly and indirectly through motivation. This suggests that enhancing teamwork and employee loyalty can lead to higher motivation, which, in turn, strengthens organizational commitment. The study's practical implications highlight the need for educational institutions to focus on improving human resource management strategies by fostering better teamwork, increasing employee loyalty, and motivating staff. These measures are vital for building a workforce that is deeply committed to the institution’s mission and vision, thus ensuring its success in the competitive educational landscape. This study contributes valuable insights for administrators aiming to optimize employee engagement and performance within educational settings.